'It becomes almost an act of defiance': indigenous Australian transformational resistance as a driver of academic achievement. Issue 4 (4th July 2017) - Pechenkina, Ekaterina
Abstract: Indigenous Australian underrepresentation in higher education remains a topical issue for social scientists, educationalists and policymakers alike, with the concept of indigenous academic success highly contested. This article is based on findings of a doctoral study investigating the drivers of indigenous Australian academic success in a large, public, research-intensive and metropolitan Australian university. It draws on the concept of transformational resistance to illuminate the forms that indigenous resistance takes and how identities of resistance performed by indigenous students complicate and speak to the students' notions of academic success. By drawing on ethnographic data, this article demonstrates how indigenous academic success is fuelled by the idea of resistance to the Western dominance, where resistance becomes the very cornerstone of indigenous achievement.